Effect of Dexmedetomidine-Induced Sleep Balance Treatment on the Chronic Refractory Primary Insomnia Patients - Ma Guo-Zhong,; Wang Rong-Hu,; Li Fa-Guo,; Feng Zheng-Quan,; Jiang Xiao-Jiang,; Xu Zhi-Qiang,; Lang Ying,; Guo Heng-Jiang,; Liu Ya-Zheng,; Zhong Dai-Qu,; Chen Ni-Ka,; Li Xu-Jun, (Journal of Basic & Applied Sciences, 2021)
Aim:To pilot study the therapeutic effect of dexmedetomidine-induced sleep balance treatment (DISBT) on the chronic refractory primary insomnia patients. Methods:Forty-two patients with chronic refractory primary insomnia were randomly divided into two groups by random number table. Patients in DISBT group were given DISBT for 3 days, while patients in the control group were given conventional treatment for 3 day. Pittsburgh sleep quality index (PSQI), the hyperarousal scale (HAS), and Hamilton anxiety scale (HAMA) were evaluated and compared between the pre-treatment and post-1-week-treatment. Sleep architecture and electroencephalogram (EEG) spectrum were also recorded and compared pre-treatment and post-treatment. Results:The scores of PSQI and HAMA in both groups after treatment were lower than those before treatment (P < 0.05), DISBT group-reduced degree were higher than those of the control group (P < 0.05). Sleep architecture of Stage 2 sleep proportion, EEG spectrum beta, and gamma relative power value in DISBT group were lower than those before treatment (P < 0.05), Stage 3 sleep proportion and delta relative power value were higher than those before treatment (P < 0.05); Sleep architecture of Stage 2 sleep proportion,beta, and gamma relative power value in control group were higher than those before treatment (P < 0.05); rapid eye movement sleep, Stage 3 sleep proportion, and delta relative power value were lower than those before treatment (P < 0.05). The total scores of the hyperarousal scale (HAS) in both groups after treatment were lower than those before treatment (P < 0.05), DISBT group-reduced degree were higher than those of the control group (P < 0.05), the extreme score, introspectiveness score, react score of HAS in control group after treatment had no statistical significance compared to those before treatment (P > 0.05), the extreme score, introspectiveness score, react score of HAS in DISBT group after treatment were lower than those before treatment (P < 0.05). Conclusion:DISBT effectively reduced the insomnia patient cortex hyperarousal level, corrected disorder of sleep-awakening pathways and easedup insomnia symptom. It is an effective method for chronic refractory primary insomnia.